2016
DOI: 10.1016/j.scitotenv.2016.03.148
|View full text |Cite
|
Sign up to set email alerts
|

Piped water consumption in Ghana: A case study of temporal and spatial patterns of clean water demand relative to alternative water sources in rural small towns

Abstract: Continuous access to adequate quantities of safe water is essential for human health and socioeconomic development. Piped water systems (PWSs) are an increasingly common type of water supply in rural African small towns. Despite providing the highest and most flexible level of service with better microbiological water quality to their users, these systems remain vulnerable to rural water sustainability challenges. We assessed temporal and spatial patterns in water consumption from public standpipes of four PWS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 26 publications
1
44
0
1
Order By: Relevance
“…For all PWSs, a nearby resident was hired by the town to sell water from the public standpipes for several hours per day in the mornings and evenings, charging water consumers on a per–use volumetric basis. More information about PWSs in the study area is found in a prior publication (Kulinkina et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For all PWSs, a nearby resident was hired by the town to sell water from the public standpipes for several hours per day in the mornings and evenings, charging water consumers on a per–use volumetric basis. More information about PWSs in the study area is found in a prior publication (Kulinkina et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Despite this limitation, we believe that the most prevalent and severe WQ problems were represented by this method, and the method can be widely and inexpensively applied to areas where no water quality information is available. Furthermore, a limited analysis of reported WQ problems and measured water quality parameters for salty taste of groundwater showed that in towns where users ubiquitously noted a salty taste, total dissolved solids, chloride and sulfate concentrations were elevated in the water samples (Kulinkina et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to the national health data of schistosomiasis in Ghana was granted based on recent research on schistosomiasis and water in Ghana (Kosinski et al 2011;Kosinaki et al, 2012;Kulinkina et al, 2016) The last systematic collection of health survey data in Ghana at the national scale and subsequently used to direct control efforts was in 2008 (Soares-Magalhaes et al, 2011). This study used detailed health data collected in 77 schools to direct post study drug distribution by interpolating predicted risk for the rest of the country.…”
Section: Discussionmentioning
confidence: 99%
“…However, these parameters define the organoleptic and aesthetic quality of water, which affects its acceptability for drinking and domestic uses (de Franca Doria, 2010). Groundwater with unpleasant taste or excess hardness, even when readily available, can drive consumers to continue using microbiologically contaminated unimproved sources (DeGabriele, 2002; Fuest, 2005; Kulinkina et al, 2016; Nyarko et al, 2007). Neither the MDG nor the SDG definition considers the organoleptic properties of improved water sources and the potential impact they may have on the utilization of these sources.…”
Section: Introductionmentioning
confidence: 99%